Pengaruh Gaya Belajar Visual Terhadap Hasil Belajar Kognitif Peserta Didik Pada Mata Pelajaran Aqidah Akhlak (Studi Di Kelas Visual MTs Al-Rohmah Karangpawitan - Salamudin, Ceceng; Multazam, Resti Risalati (STAI Al-Musaddadiyah Garut, 2023)
Cognitive learning outcomes are a crucial component in education, serving to measure how well students have acquired knowledge and skills during the learning process. However, many students still exhibit low performance in cognitive learning outcomes. One primary reason for this underperformance is the misalignment between teaching styles and the students' learning styles, which adversely affects their academic results. Adopting a visual learning style is proposed as an effective solution to enhance cognitive learning outcomes. MTs Al-Rohmah implements a visual learning approach, aiming to help students absorb and process information more effectively, thereby achieving optimal learning outcomes. This study aims to describe the impact of visual learning style on cognitive learning outcomes in the subject of Aqidah Akhlak for Visual Class students at MTs Al-Rohmah Karangpawitan Garut. The research adopts a descriptive quantitative approach. Data collection was conducted through observation and the distribution of questionnaires to 30 respondents. The collected data were analyzed using statistical methods. The results indicate that the cognitive learning outcomes in the subject of Aqidah Akhlak at MTs Al-Rohmah are categorized as